Factors for hesitancy towards vaccination against COVID-19 among the adult population in Puducherry, India - a cross sectional study - Raja Jeyapal Dinesh; Rajendran Dhanalakshmi; Priskilla Johnson Jency; Adinarayanan Srividya; Balakrishnan Vijayakumar; Ashwani Kumar (BMC, 2023)
Abstract Background Vaccine hesitancy is a complex phenomenon that threatens global health. Present-day communication technology has paved the way for self-education but also contributed to the infodemic surrounding vaccination. This has resulted in pockets of people who are reluctant, refuse recommended vaccinations, or choose to delay being vaccinated. The present study was designed to estimate the magnitude of hesitancy towards the COVID-19 vaccination and determine its associated factors in the community. Methods This cross-sectional study was conducted among 776 adults aged ≥ 18 years in 15 clusters in Puducherry district, India, between March 2022 and May 2022. Face-to-face interviews were conducted using a validated, structured questionnaire. Socio-demographic variables, co-morbidities, attitudes towards vaccination, etc., were expressed as frequencies and percentages. Vaccine hesitancy was dichotomized with the median score as the cut-off and reported as a proportion with a 95% confidence interval. Univariate and multivariate analyses were carried out to determine the factors associated with vaccine hesitancy. Results The mean age of participants was 43.3 ± 14.8 years, with the majority being female (67.0%). Nearly 92.4%, 74.4%, and 0.5% of participants received their first, second, and precautionary doses, respectively, during the study period. Among the unvaccinated, 93.2% were unwilling to receive any dose of vaccination. More than half of the participants were hesitant towards vaccination, according to the vaccine hesitancy scale. Participants aged above 45 years were less hesitant, while those educated up to school level, belonging to the upper socio-economic class, never tested for COVID-19 in the past, and having a negative attitude towards vaccination were significantly associated with higher vaccine hesitancy. Conclusions It is imperative to address vaccine hesitancy by alleviating existing fears and misconceptions in the community through efficient communication strategies to win the fight against current as well as future public health emergencies.